Acute Kidney Injury (AKI) et causa Sindrom Nefrotik dengan Komponen Nefritik pada Anak: Laporan Kasus - Auriva Renasha Suherman; Shinta Nareswari (Medula, 2026)
Acute Kidney Injury (AKI) is a clinical syndrome characterized by a sudden decline in kidney function, resulting in disturbances of fluid and electrolyte balance and the accumulation of metabolic waste products. In children, AKI may occur secondary to various underlying conditions, including nephrotic syndrome with nephritic components. This case report aims to describe the clinical manifestations, diagnostic evaluation, and management of AKI in a child with nephrotic syndrome accompanied by nephritic features. A 12-year-old girl presented with a 10-day history of fever, accompanied by swelling of the face, lower extremities, and genitalia, abdominal distension and pain, joint pain, oliguria, and reddish, foamy urine. Physical examination revealed stage 2 hypertension, periorbital edema, bilateral lower-extremity edema, labia majora edema, ascites, and anemic conjunctivae. Laboratory findings demonstrated anemia, hypoalbuminemia, elevated blood urea and serum creatinine levels, hyperkalemia, hypocalcemia, and partially compensated metabolic acidosis. Reduced glomerular filtration rate and oliguria supported the diagnosis of stage 2 AKI according to the Kidney Disease: Improving Global Outcomes (KDIGO) criteria. The patient was diagnosed with AKI secondary to nephrotic syndrome with nephritic components and received comprehensive treatment consisting of intravenous fluid therapy, furosemide, captopril, prednisone, antibiotics, and supportive management. Comprehensive treatment and close monitoring were required to improve the patient's clinical condition, prevent complications, and preserve quality of life. This case highlights the importance of early recognition and multidisciplinary management of pediatric AKI associated with nephrotic syndrome and nephritic components to prevent progressive renal impairment.